Point of contact ebook - Maden, Mike (Jack Ryan Jr., 2017)
Jack Ryan Jr. finds himself on the front lines of cyber war and in the eye of a killer storm in this thriller in Tom Clancy's #1  New York Times bestselling series. A former U.S. senator and defense contractor needs someone to look over the books of Dalfan Technologies, a Singapore company—quickly. He turns to Jack Ryan, Jr., and Paul Brown, two employees of one of the best financial analysis firms in the country, which also happens to be the cover for The Campus, a top secret American intelligence agency. Brown has no idea that Jack works for The Campus. Jack has no idea that the awkward accountant has been tasked with uploading a cyberwarfare program into the highly secure Dalfan Technologies mainframe on behalf of the CIA. On the verge of mission success, Brown discovers a game within the game, and the people who now want to kill him are as deadly as the cyclone bearing down on the island nation. Together Ryan and Brown race to escape both the dangerous storm and a team of trained assassins in order to prevent a global catastrophe, even at the cost of their own lives.